Renewable Energy Support, Negative Prices, and Real-time Pricing - Michael Pahle; Wolf-Peter Schill; Christian Gambardella; Oliver Tietjen (The Energy Journal, 2016)
We analyze the welfare effects of two different renewable support schemes designed to achieve a given target for the share of fluctuating renewable electricity generation: a feed-in premium (FiP), which can induce negative wholesale prices, and a capacity premium (CP), which does not. For doing so we use a stylized economic model that differentiates between real-time and flat-rate pricing and is loosely calibrated on German market data. Counter-intuitively, we find that distortions through induced negative prices do not reduce the net consumer surplus of the FiP relative to the CP. Rather, the FiP performs better under all assumptions considered. The reason is that increased use of renewables under the FiP, particularly in periods of negative prices, leads to a reduction of required renewable capacity and respective costs. This effect dominates larger deadweight losses of consumer surplus generated by the FiP compared to the CP. Furthermore, surplus gains experienced by consumers who switch from flat-rate to real-time pricing are markedly higher under the FiP, which might be interpreted as greater incentives to enable such switching. While our findings are primarily of theoretical nature and the full range of implications of negative prices needs to be carefully considered, we hope that our analysis makes policy-makers more considerate of their potential benefits.
Keywords: Q41; Q42; L11; D40; D12; D62; D61; D24; 330; RES support schemes; Induces negative prices; Real-time pricing